Length of stay and trauma center finances: A disparity of payer source at a Level I trauma center. Issue 4 (4th April 2022) - Chavez, Marin A.; Bogert, James N.; Soe-Lin, Hahn; Jacobs, Jordan V.; Chapple, Kristina M.; Weinberg, Jordan A.
Abstract : We evaluated the impact of the geometric length of stay on contribution margin in trauma patients at our Level I Center. For cases exceeding GMLOS, Medicare and Medicaid payers were less likely than commercial payers to have a positive contribution margin. Abstract : BACKGROUND: In an effort to reduce costs, hospitals focus efforts on reducing length of stay (LOS) and often benchmark LOS against the geometric LOS (GMLOS) as predicted by the assigned diagnosis-related group (DRG) used by the Centers for Medicare and Medicaid Services. The objective of this cross-sectional study was to evaluate the impact of exceeding GMLOS on hospital profit/loss with respect to payer source. METHODS: Contribution margin for each insured patient admitted to a Level I trauma center between July 1, 2016, and June 30, 2019, was determined. Age, ethnicity, race, DRG weight, DRG version, injury severity, intensive care unit admission status, mechanical ventilation, payer, exceeding GMLOS, and the interaction between payer and exceeding the GMLOS were regressed on contribution margin to determine significant predictors of positive contribution margin. RESULTS: Among 2, 449 insured trauma patients, the distribution of payers was Medicaid (54.6%), Medicare (24.0%), and commercial (21.4%). Thirty-five percent (n = 867) of patient LOS exceeded GMLOS. Exceeding GMLOS by 10 or more days was significantly more likely for Medicaid and Medicare patients in stepwise fashion (commercial, 2.7%; Medicaid, 4.5%; Medicare, 6.0%; p = 0.030). Median contribution margin was positive for commercially insured patients (16, 913) and negative for Medicaid (−8, 979) and Medicare (−2, 145) patients. Adjusted multivariate modeling demonstrated that when exceeding GMLOS, Medicare and Medicaid cases were less likely than commercial payers to have a positive contribution margin ( p < 0.001 and p < 0.001). CONCLUSION: Government-insured patients, despite having a payer source, are a financial burden to a trauma center. Excess LOS among government insured patients, but not the commercially insured, exacerbates financial loss. A shift toward a greater proportion of government insured patients may result in a significant fiscal liability for a trauma center. LEVEL OF EVIDENCE: Economic and Value-Based Evaluation, Level III. Abstract :